Growth of Falcataria moluccana and Albizia chinensis seedling under aluminum exposure - Mohammad Agus Salim; LULUK SETYANINGSIH; IMAM WAHYUDI; SRI WILARSO BUDI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Salim MA, Setyaningsih L, Wahyudi I, Budi SW. 2021. Growth of Falcataria moluccana and Albizia chinensis seedling under aluminum exposure. Biodiversitas 22: 3693-3701. Aluminum (Al) is an element found in acid soils and is one of the limiting factors for plant growth. This study aims to examine the growth of Falcataria moluccana (Miq.) Barneby & J.W.Grimes and Albizia chinensis (Osbeck) Merr seedlings under exposure of aluminum. This study used an one-factor completely randomized design (Al concentration) consisting of 5 levels, namely 0, 2, 4, 6, and 8 mM. Each treatment was repeated 3 times and each replication consisted of 3 plant units. The results showed that the Al exposure treatment gave significant differences in the growth of height, root length, dry weight (root, shoot, and total) of F. moluccana and A. chinensis seedlings. The 2 mM Al concentration stimulated the growth of height, root length and dry weight (root, shoot, and total) of A. chinensis seedlings. The tolerance index for F. moluccana and A. chinensis seedlings was highest when the Al 2 mM concentration was 147.55% and 115.32%, respectively. 2 mM Al exposure treatment increased the chlorophyll content a, b, total chlorophyll and carotenoids of F. moluccana and A. chinensis seedlings. Al exposure treatment did not significantly differ from the rate of photosynthesis and MDA content in F. moluccana and A. chinensis seedlings. The Al content in the roots was higher than in the shoots, and the increase in Al concentration increased the Al content in the roots and shoots of F. moluccana and A. chinensis seedlings.